Unique defect evolution during the plastic deformation of a metal matrix composite. (15th March 2019) - Liu, Yanfang; Wang, Fang; Cao, Yang; Nie, Jinfeng; Zhou, Hao; Yang, Huabing; Liu, Xiangfa; An, Xianghai; Liao, Xiaozhou; Zhao, Yonghao; Zhu, Yuntian
Abstract: During the plastic deformation of a metal matrix composite (MMC) containing non-deformable particles, high dislocation density and strong back stresses are expected because the particles help with blocking and accumulating dislocations. Here we report that the MMC has lower, instead of higher, dislocation density than the corresponding monolithic matrix material when they are deformed to high plastic strains, because smaller sub-grains in the MMC lowered dislocation generation rate and meanwhile promoted the dislocation interaction and annihilation in the matrix. This unique defect density evolution is a hitherto unknown but important factor affecting the mechanical properties of MMCs. Graphical abstract: Unlabelled Image